Effects of surgical implantation of electronic tags in fishes: a review and meta-analysis - Mitchell B. Shorgan; Graham D. Raby; Amber L. Fedus; Bradley E. Howell; Laura S. E. Haniford; Leah C. Howitt; Natalie V. Klinard; Jordan K. Matley; Jacob W. Brownscombe; Steven J. Cooke; Aaron T. Fisk (Reviews in Fish Biology and Fisheries, 2026)

Explaining state investment in drinking water infrastructure for disadvantaged communities, 1997-2016 - Xi Chen; Jonathan M. Fisk; John C. Morris; Ryan P. Scott (Utilities Policy, 2026)

Species nativeness as a cultural paradigm in conservation - Lily M. van Eeden; Jeff Vance Martin; Jonathan Fisk; Lisa Lehnen; Erle C. Ellis; Michael C. Gavin; Adam C. Landon; Lincoln R. Larson; Kirsten M. Leong; Wayne Linklater; Christopher K. Williams; Richard E.W. Berl (Biological Conservation, 2025)

Reduced intraspecific variation in lake trout food webs under warmer temperatures and smaller ecosystem sizes - Cassandra J. Kotsopoulos; Marie Gutgesell; Matthew M. Guzzo; Thomas A. Johnston; Tyler D. Tunney; Timothy J. Bartley; Bailey C. McMeans; Mark S. Ridgway; Paul J. Blanchfield; Aaron T. Fisk; Kevin S. McCann (Ecology, 2025)
Food web theory has illustrated that mobile top predators, such as lake trout ( Salvelinus namaycush ), can be potent stabilizers of food webs due to their ability to shift foraging behaviors in response to changing conditions. Consistent with this, research has demonstrated that mean lake trout food web attributes (i.e., trophic position and nearshore coupling) structurally change across environmental gradients; however, intraspecific variation in these attributes across gradients has not been fully explored. Here, we used stable isotope‐based food web metrics to investigate how both mean and intraspecific variation in trophic structure changes in Canadian boreal shield lakes across gradients in ecosystem size, temperature, and competition. Consistent with earlier findings, we find nearshore coupling decreases and trophic position increases with warmer summer climate. In contrast to previous findings, increasing lake area predicted increased nearshore coupling and was not associated with lake trout trophic position. Our results show that warmer temperatures and smaller ecosystem sizes reduce the expression of intraspecific variation in food web structures. Specifically, larger lakes increased variation in nearshore coupling and trophic position, resulting in larger niche areas, and warmer lakes reduced variation in nearshore coupling and tended to generate smaller niche areas. Interestingly, we found little evidence for the relative abundance of lake trout or other predator taxa (surrogates of intra‐ and interspecific competition) influencing mean and variance in lake trout trophic structure. Intraspecific variation can promote ecosystem resilience by enabling diverse individual responses that help buffer populations against environmental change. Therefore, reduction in intraspecific variation in smaller, warmer lakes may have undesirable consequences for lake trout and the biota in these Canadian boreal shield lakes, leaving these ecosystems less able to adjust to future perturbations.

Nitrogen and phosphorus co‐limitation of tree growth in northern hardwood forests - Noah M. Blumenthal; M. Henry H. Stevens; Shinjini Goswami; Ruth D. Yanai; Timothy J. Fahey; Melany C. Fisk (Ecology, 2025)
Nutrient limitation of forest growth has been difficult to predict, and in temperate forests, long‐term tests of single‐nutrient versus multiple‐element limitation are few. Nutrient co‐limitation is the expected outcome of the ability of plants to adjust allocation to minimize limitation by any single resource. Nutrient limitation of productivity in northern hardwood forests was predicted by the Multiple Element Limitation (MEL) model to shift over time since harvest from single limitation by N to P at ~30 years and then, in mature forests, to co‐limitation by N and P. Our work tested those predictions for tree growth in a fully factorial N and P addition experiment in 13 forest stands that we grouped in young (20–30 years), mid‐age (40–50 years), and mature (>100 years old) age classes in New Hampshire, USA. Over 8 years of treatment, we found evidence of additive co‐limitation of tree growth by N and P. We did not find evidence that limitation varied with time since disturbance. Our results suggest that processes contributing to co‐limitation in these northern hardwood forests are effective across stands that vary widely in N status and are not sensitive to disturbance by forest harvest over time periods of several decades.

Fatty acid carbon isotopes as tracers of trophic structure and contaminant biomagnification in Arctic marine food webs - Adam F. Pedersen; Aaron T. Fisk; Bailey C. McMeans; Rune Dietz; Christian Sonne; Aqqalu Rosing-Asvid; Steven H. Ferguson; Melissa A. McKinney (Science of The Total Environment, 2025)

Smartphone-based hyperspectral imaging for ice sheet and proglacial applications in South-West Greenland - M.B. Stuart; M. Davies; C. Fisk; E. Allen; A.J. Sole; R. Ing; M.J. Hobbs; J.R. Willmott (Science of The Total Environment, 2024)

Elevated P availability slows N recycling in northern hardwood forests - Shinjini Goswami; Melany C. Fisk (Forest Ecology and Management, 2024)

Salt type, sugar addition, and system type in intensive RAS for Pacific white shrimp (Litopenaeus vannamei) production - Shrijan Bajracharya; Jill C. Fisk; Leo J. Fleckenstein; Andrew J. Ray (Aquaculture, 2024)

Co-limitation of Fine Root Growth by Nitrogen and Phosphorus in Early Successional Northern Hardwood Forests - Shiyi Li; Melany C. Fisk; Ruth D. Yanai; Timothy J. Fahey (Ecosystems, 2024)

Un‘covering’ blanket bonds: Assessing the adoption of blanket bonds across the states - Nurun Naher; Adam P. Mayer; Jonathan M. Fisk; John C. Morris (The Extractive Industries and Society, 2023)

The effects of stocking density and artifical substrate on production of pacific white shrimp Litopenaeus vannamei and water quality dynamics in greenhouse-based biofloc systems - Nathan A. Kring; Leo J. Fleckenstein; Thomas W. Tierney; Jill C. Fisk; Benjamin C. Lawson; Andrew J. Ray (Aquacultural Engineering, 2023)

Evidence for P limitation in eight northern hardwood stands: Foliar concentrations and resorption by three tree species in a factorial N by P addition experiment - Kara E. Gonzales; Ruth D. Yanai; Timothy J. Fahey; Melany C. Fisk (Forest Ecology and Management, 2023)

Subsidy accessibility drives asymmetric food web responses - Marie Gutgesell; Bailey C. McMeans; Matthew M. Guzzo; Valesca de Groot; Aaron T. Fisk; Timothy B. Johnson; Kevin S. McCann (Ecology, 2022)
Global change is fundamentally altering flows of natural and anthropogenic subsidies across space and time. After a pointed call for research on subsidies in the 1990s, an industry of empirical work has documented the ubiquitous role subsidies play in ecosystem structure, stability, and function. Here, we argue that physical constraints (e.g., water temperature) and species traits can govern a species' accessibility to resource subsidies, which has been largely overlooked in the subsidy literature. We examined the input of a high‐quality, point‐source anthropogenic subsidy (aquaculture feed) into a recipient freshwater lake food web. Using a combined bio‐tracer approach, we detect a gradient in accessibility of the anthropogenic subsidy within the surrounding food web driven by the thermal preferences of three constituent species, effectively rewiring the recipient lake food web. Because aquaculture is predicted to increase significantly in coming decades to support growing human populations, and global change is altering temperature regimes, then this form of food web alteration may be expected to occur frequently. We argue that subsidy accessibility is a key characteristic of recipient food web interactions that must be considered when trying to understand the impacts of subsidies on ecosystem stability and function under continued global change.

Fine Root Growth Increases in Response to Nitrogen Addition in Phosphorus-limited Northern Hardwood Forests - Shan Shan; Hannah Devens; Timothy J. Fahey; Ruth D. Yanai; Melany C. Fisk (Ecosystems, 2022)

Using untapped telemetry data to explore the winter biology of freshwater fish - J. E. Marsden; P. J. Blanchfield; J. L. Brooks; T. Fernandes; A. T. Fisk; M. H. Futia; B. L. Hlina; S. V. Ivanova; T. B. Johnson; N. V. Klinard; C. C. Krueger; S. M. Larocque; et al. (Reviews in Fish Biology and Fisheries, 2021)

Interactive Effects of White-Tailed Deer, an Invasive Shrub, and Exotic Earthworms on Leaf Litter Decomposition - Michael B. Mahon; Melany C. Fisk; Thomas O. Crist (Ecosystems, 2020)

Phosphorus limitation of aboveground production in northern hardwood forests - Shinjini Goswami; Melany C. Fisk; Matthew A. Vadeboncoeur; Mariann Garrison‐Johnston; Ruth D. Yanai; Timothy J. Fahey (Ecology, 2018)
Forest productivity on glacially derived soils with weatherable phosphorus (P) is expected to be limited by nitrogen (N), according to theories of long‐term ecosystem development. However, recent studies and model simulations based on resource optimization theory indicate that productivity can be co‐limited by N and P. We conducted a full factorial N × P fertilization experiment in 13 northern hardwood forest stands of three age classes in central New Hampshire, USA , to test the hypothesis that forest productivity is co‐limited by N and P. We also asked whether the response of productivity to N and P addition differs among species and whether differential species responses contribute to community‐level co‐limitation. Plots in each stand were fertilized with 30 kg N·ha −1 ·yr −1 , 10 kg P·ha −1 ·yr −1 , N + P, or neither nutrient (control) for four growing seasons. The productivity response to treatments was assessed using per‐tree annual relative basal area increment ( RBAI ) as an index of growth. RBAI responded significantly to P ( P = 0.02) but not to N ( P = 0.73). However, evidence for P limitation was not uniform among stands. RBAI responded to P fertilization in mid‐age ( P = 0.02) and mature ( P = 0.07) stands, each taken as a group, but was greatest in N‐fertilized plots of two stands in these age classes, and there was no significant effect of P in the young stands. Both white birch ( Betula papyrifera Marsh.) and beech ( Fagus grandifolia Ehrh.) responded significantly to P; no species responded significantly to N. We did not find evidence for N and P co‐limitation of tree growth. The response to N + P did not differ from that to P alone, and there was no significant N × P interaction ( P = 0.68). Our P limitation results support neither the N limitation prediction of ecosystem theory nor the N and P co‐limitation prediction of resource optimization theory, but could be a consequence of long‐term anthropogenic N deposition in these forests. Inconsistencies in response to P suggest that successional status and variation in site conditions influence patterns of nutrient limitation and recycling across the northern hardwood forest landscape.

Reduced snow cover alters root‐microbe interactions and decreases nitrification rates in a northern hardwood forest - Patrick O. Sorensen; Pamela H. Templer; Lynn Christenson; Jorge Duran; Timothy Fahey; Melany C. Fisk; Peter M. Groffman; Jennifer L. Morse; Adrien C. Finzi (Ecology, 2016)
Snow cover is projected to decline during the next century in many ecosystems that currently experience a seasonal snowpack. Because snow insulates soils from frigid winter air temperatures, soils are expected to become colder and experience more winter soil freeze‐thaw cycles as snow cover continues to decline. Tree roots are adversely affected by snowpack reduction, but whether loss of snow will affect root‐microbe interactions remains largely unknown. The objective of this study was to distinguish and attribute direct (e.g., winter snow‐ and/or soil frost‐mediated) vs. indirect (e.g., root‐mediated) effects of winter climate change on microbial biomass, the potential activity of microbial exoenzymes, and net N mineralization and nitrification rates. Soil cores were incubated in situ in nylon mesh that either allowed roots to grow into the soil core (2 mm pore size) or excluded root ingrowth (50 μm pore size) for up to 29 months along a natural winter climate gradient at Hubbard Brook Experimental Forest, NH ( USA ). Microbial biomass did not differ among ingrowth or exclusion cores. Across sampling dates, the potential activities of cellobiohydrolase, phenol oxidase, and peroxidase, and net N mineralization rates were more strongly related to soil volumetric water content ( P 0.05; R 2 = 0.25–0.46) than to root biomass, snow or soil frost, or winter soil temperature ( R 2 P 0.01; R 2 = 0.28), suggesting that trees compensate for overwinter root mortality caused by soil freezing by re‐allocating resources towards root production. At the sites with the deepest snow cover, root ingrowth reduced nitrification rates by 30% ( P 0.01), showing that tree roots exert significant influence over nitrification, which declines with reduced snow cover. If soil freezing intensifies over time, then greater compensatory root growth may reduce nitrification rates directly via plant‐microbe N competition and indirectly through a negative feedback on soil moisture, resulting in lower N availability to trees in northern hardwood forests.

Distinct patterns of Arctic cod (Boreogadus saida) presence and absence in a shallow high Arctic embayment, revealed across open-water and ice-covered periods through acoustic telemetry - S. T. Kessel; N. E. Hussey; R. E. Crawford; D. J. Yurkowski; C. V. O’Neill; A. T. Fisk (Polar Biology, 2016)

Spatial and temporal variation of an ice-adapted predator’s feeding ecology in a changing Arctic marine ecosystem - David J. Yurkowski; Steven H. Ferguson; Christina A. D. Semeniuk; Tanya M. Brown; Derek C. G. Muir; Aaron T. Fisk (Oecologia, 2016)

Infection and pathology in Queensland grouper, Epinephelus lanceolatus , (Bloch), caused by exposure to Streptococcus agalactiae via different routes - J Delamare‐Deboutteville; R Bowater; K Condon; A Reynolds; A Fisk; F Aviles; A C Barnes (Journal of Fish Diseases, 2015)
Since 2007, 96 wild Queensland groupers, Epinephelus lanceolatus , (Bloch), have been found dead in NE Australia. In some cases, Streptococcus agalactiae (Group B Streptococcus , GBS ) was isolated. At present, a GBS isolate from a wild grouper case was employed in experimental challenge trials in hatchery‐reared Queensland grouper by different routes of exposure. Injection resulted in rapid development of clinical signs including bilateral exophthalmia, hyperaemic skin or fins and abnormal swimming. Death occurred in, and GBS was re‐isolated from, 98% fish injected and was detected by PCR in brain, head kidney and spleen from all fish, regardless of challenge dose. Challenge by immersion resulted in lower morbidity with a clear dose response. Whilst infection was established via oral challenge by admixture with feed, no mortality occurred. Histology showed pathology consistent with GBS infection in organs examined from all injected fish, from fish challenged with medium and high doses by immersion, and from high‐dose oral challenge. These experimental challenges demonstrated that GBS isolated from wild Queensland grouper reproduced disease in experimentally challenged fish and resulted in pathology that was consistent with that seen in wild Queensland grouper infected with S. agalactiae .

Soil nitrogen affects phosphorus recycling: foliar resorption and plant–soil feedbacks in a northern hardwood forest - Craig R. See; Ruth D. Yanai; Melany C. Fisk; Matthew A. Vadeboncoeur; Braulio A. Quintero; Timothy J. Fahey (Ecology, 2015)
Previous studies have attempted to link foliar resorption of nitrogen and phosphorus to their respective availabilities in soil, with mixed results. Based on resource optimization theory, we hypothesized that the foliar resorption of one element could be driven by the availability of another element. We tested various measures of soil N and P as predictors of N and P resorption in six tree species in 18 plots across six stands at the Bartlett Experimental Forest, New Hampshire, USA. Phosphorus resorption efficiency ( P P = 0.01) increased with soil N content to 30 cm depth, suggesting that trees conserve P based on the availability of soil N. Phosphorus resorption also increased with soil P content, which is difficult to explain based on single‐element limitation, but follows from the correlation between soil N and soil P. The expected single‐element relationships were evident only in the O horizon: P resorption was high where resin‐available P was low in the Oe ( P P P

Regional movement patterns of a small‐bodied shark revealed by stable‐isotope analysis - S. E. M. Munroe; M. R. Heupel; A. T. Fisk; M. Logan; C. A. Simpfendorfer (Journal of Fish Biology, 2015)
This study used stable‐isotope analysis to define the nearshore regional residency and movements of the small‐bodied Australian sharpnose shark Rhizoprionodon taylori . Plasma and muscle δ 13 C and δ 15 N of R. taylori were collected from across five embayments and compared with values of seagrass and plankton from each bay. Linear distances between adjacent bays ranged from 30 to 150 km. There was a positive geographic correlation between R. taylori tissue and environmental δ 13 C values. Populations with the highest tissue δ 15 N were collected from bays that had the highest environmental δ 15 N values. These results suggest that R. taylori did not forage more than 100 km away from their capture location within 6 months to 1 year. The successful application of isotope analysis to define R. taylori movement demonstrates that this technique may be used in addition to traditional methods to study the movement of sharks, even within similar habitats across regionally small spatial scales (

Earthworms Reduce Biotic 15-Nitrogen Retention in Northern Hardwood Forests - Holly A. Ewing; Amy R. Tuininga; Peter M. Groffman; Kathleen C. Weathers; Timothy J. Fahey; Melany C. Fisk; Patrick J. Bohlen; Esteban Suarez (Ecosystems, 2015)

Winter climate change affects growing‐season soil microbial biomass and activity in northern hardwood forests - Jorge Durán; Jennifer L. Morse; Peter M. Groffman; John L. Campbell; Lynn M. Christenson; Charles T. Driscoll; Timothy J. Fahey; Melany C. Fisk; Myron J. Mitchell; Pamela H. Templer (Global Change Biology, 2014)
Understanding the responses of terrestrial ecosystems to global change remains a major challenge of ecological research. We exploited a natural elevation gradient in a northern hardwood forest to determine how reductions in snow accumulation, expected with climate change, directly affect dynamics of soil winter frost, and indirectly soil microbial biomass and activity during the growing season. Soils from lower elevation plots, which accumulated less snow and experienced more soil temperature variability during the winter (and likely more freeze/thaw events), had less extractable inorganic nitrogen (N), lower rates of microbial N production via potential net N mineralization and nitrification, and higher potential microbial respiration during the growing season. Potential nitrate production rates during the growing season were particularly sensitive to changes in winter snow pack accumulation and winter soil temperature variability, especially in spring. Effects of elevation and winter conditions on N transformation rates differed from those on potential microbial respiration, suggesting that N‐related processes might respond differently to winter climate change in northern hardwood forests than C‐related processes.

Corrigendum to Hussey et al . () - Nigel E. Hussey; M. Aaron MacNeil; Bailey C. McMeans; Jill A. Olin; Sheldon F.J. Dudley; Geremy Cliff; Sabine P. Wintner; Sean T. Fennessy; Aaron T. Fisk (Ecology Letters, 2014)

A review of detection range testing in aquatic passive acoustic telemetry studies - S. T. Kessel; S. J. Cooke; M. R. Heupel; N. E. Hussey; C. A. Simpfendorfer; S. Vagle; A. T. Fisk (Reviews in Fish Biology and Fisheries, 2014)

First record of living Manta alfredi × Manta birostris hybrid - R. P. Walter; S. T. Kessel; N. Alhasan; A. T. Fisk; D. D. Heath; T. Chekchak; R. Klaus; M. Younis; G. Hill; B. Jones; C. D. Braun; M. L. Berumen; et al. (Marine Biodiversity, 2014)

Rescaling the trophic structure of marine food webs - Nigel E. Hussey; M. Aaron MacNeil; Bailey C. McMeans; Jill A. Olin; Sheldon F.J. Dudley; Geremy Cliff; Sabine P. Wintner; Sean T. Fennessy; Aaron T. Fisk (Ecology Letters, 2014)
Measures of trophic position ( TP ) are critical for understanding food web interactions and human‐mediated ecosystem disturbance. Nitrogen stable isotopes (δ 15 N) provide a powerful tool to estimate TP but are limited by a pragmatic assumption that isotope discrimination is constant (change in δ 15 N between predator and prey, Δ 15 N = 3.4‰), resulting in an additive framework that omits known Δ 15 N variation. Through meta‐analysis, we determine narrowing discrimination from an empirical linear relationship between experimental Δ 15 N and δ 15 N values of prey consumed. The resulting scaled Δ 15 N framework estimated reliable TP s of zooplanktivores to tertiary piscivores congruent with known feeding relationships that radically alters the conventional structure of marine food webs. Apex predator TP estimates were markedly higher than currently assumed by whole‐ecosystem models, indicating perceived food webs have been truncated and species‐interactions over simplified. The scaled Δ 15 N framework will greatly improve the accuracy of trophic estimates widely used in ecosystem‐based management.

ERP evidence suggests executive dysfunction in ecstasy polydrug users - C. A. Roberts; S. H. Fairclough; J. E. Fisk; F. Tames; C. Montgomery (Psychopharmacology, 2013)

The role of Greenland sharks (Somniosus microcephalus) in an Arctic ecosystem: assessed via stable isotopes and fatty acids - Bailey C. McMeans; Michael T. Arts; Christian Lydersen; Kit M. Kovacs; Haakon Hop; Stig Falk-Petersen; Aaron T. Fisk (Marine Biology, 2013)

Seasonal patterns in fatty acids of Calanus hyperboreus (Copepoda, Calanoida) from Cumberland Sound, Baffin Island, Nunavut - Bailey C. McMeans; Michael T. Arts; Scott A. Rush; Aaron T. Fisk (Marine Biology, 2012)

Stable isotopes and elasmobranchs: tissue types, methods, applications and assumptions - N. E. Hussey; M. A. MacNeil; J. A. Olin; B. C. McMeans; M. J. Kinney; D. D. Chapman; A. T. Fisk (Journal of Fish Biology, 2012)
Stable‐isotope analysis (SIA) can act as a powerful ecological tracer with which to examine diet, trophic position and movement, as well as more complex questions pertaining to community dynamics and feeding strategies or behaviour among aquatic organisms. With major advances in the understanding of the methodological approaches and assumptions of SIA through dedicated experimental work in the broader literature coupled with the inherent difficulty of studying typically large, highly mobile marine predators, SIA is increasingly being used to investigate the ecology of elasmobranchs (sharks, skates and rays). Here, the current state of SIA in elasmobranchs is reviewed, focusing on available tissues for analysis, methodological issues relating to the effects of lipid extraction and urea, the experimental dynamics of isotopic incorporation, diet‐tissue discrimination factors, estimating trophic position, diet and mixing models and individual specialization and niche‐width analyses. These areas are discussed in terms of assumptions made when applying SIA to the study of elasmobranch ecology and the requirement that investigators standardize analytical approaches. Recommendations are made for future SIA experimental work that would improve understanding of stable‐isotope dynamics and advance their application in the study of sharks, skates and rays.

Biology of the Greenland shark Somniosus microcephalus - M. A. MacNeil; B. C. McMeans; N. E. Hussey; P. Vecsei; J. Svavarsson; K. M. Kovacs; C. Lydersen; M. A. Treble; G. B. Skomal; M. Ramsey; A. T. Fisk (Journal of Fish Biology, 2012)
Greenland shark Somniosus microcephalus is a potentially important yet poorly studied cold‐water species inhabiting the North Atlantic and Arctic Oceans. Broad‐scale changes in the Arctic ecosystem as a consequence of climate change have led to increased attention on trophic dynamics and the role of potential apex predators such as S. microcephalus in the structure of Arctic marine food webs. Although Nordic and Inuit populations have caught S. microcephalus for centuries, the species is of limited commercial interest among modern industrial fisheries. Here, the limited historical information available on S. microcephalus occurrence and ecology is reviewed and new catch, biological and life‐history information from the Arctic and North Atlantic Ocean region is provided. Given the considerable by‐catch rates in high North Atlantic Ocean latitudes it is suggested that S. microcephalus is an abundant predator that plays an important, yet unrecognized, role in Arctic marine ecosystems. Slow growth and large pup sizes, however, may make S. microcephalus vulnerable to increased fishing pressure in a warming Arctic environment.

Harmonization of land-use scenarios for the period 1500–2100: 600 years of global gridded annual land-use transitions, wood harvest, and resulting secondary lands - G. C. Hurtt; L. P. Chini; S. Frolking; R. A. Betts; J. Feddema; G. Fischer; J. P. Fisk; K. Hibbard; R. A. Houghton; A. Janetos; C. D. Jones; G. Kindermann; et al. (Climatic Change, 2011)

Rhizosphere disturbance influences fungal colonization and community development on dead fine roots - Melany C. Fisk; Timothy J. Fahey; James H. Sobieraj; Andria Costello Staniec; Thomas O. Crist (Plant and Soil, 2011)

Transport of Carbon and Nitrogen Between Litter and Soil Organic Matter in a Northern Hardwood Forest - Timothy J. Fahey; Joseph B. Yavitt; Ruth E. Sherman; Peter M. Groffman; Melany C. Fisk; John C. Maerz (Ecosystems, 2011)

Genetic resilience of Daphnia populations following experimental removal of introduced fish - Leigh C. Latta; Debra L. Fisk; Roland A. Knapp; Michael E. Pfrender (Conservation Genetics, 2010)

Climate Variation and Soil Carbon and Nitrogen Cycling Processes in a Northern Hardwood Forest - Peter M. Groffman; Janet P. Hardy; Melany C. Fisk; Timothy J. Fahey; Charles T. Driscoll (Ecosystems, 2009)

Preliminary assessment of Greenland halibut diet in Cumberland Sound using stable isotopes - Susan T. Dennard; Bailey C. McMeans; Aaron T. Fisk (Polar Biology, 2009)

Experimental snowpack reduction alters organic matter and net N mineralization potential of soil macroaggregates in a northern hardwood forest - J. Megan Steinweg; Melany C. Fisk; Benjamin McAlexander; Peter M. Groffman; Janet P. Hardy (Biology and Fertility of Soils, 2008)

Calcium Additions and Microbial Nitrogen Cycle Processes in a Northern Hardwood Forest - Peter M. Groffman; Melany C. Fisk; Charles T. Driscoll; Gene E. Likens; Timothy J. Fahey; Christopher Eagar; Linda H. Pardo (Ecosystems, 2006)

Earthworm Invasion, Fine-root Distributions, and Soil Respiration in North Temperate Forests - Melany C. Fisk; Timothy J. Fahey; Peter M. Groffman; Patrick J. Bohlen (Ecosystems, 2004)

Influence of Earthworm Invasion on Redistribution and Retention of Soil Carbon and Nitrogen in Northern Temperate Forests - Patrick J. Bohlen; Derek M. Pelletier; Peter M. Groffman; Timothy J. Fahey; Melany C. Fisk (Ecosystems, 2004)

Exotic Earthworm Invasion and Microbial Biomass in Temperate Forest Soils - Peter M. Groffman; Patrick J. Bohlen; Melany C. Fisk; Timothy J. Fahey (Ecosystems, 2004)

Effects of Exotic Earthworms on Soil Phosphorus Cycling in Two Broadleaf Temperate Forests - Esteban R. Surez; Derek M. Pelletier; Timothy J. Fahey; Peter M. Groffman; Patrick J. Bohlen; Melany C. Fisk (Ecosystems, 2004)

Ecosystem Consequences of Exotic Earthworm Invasion of North Temperate Forests - Patrick J. Bohlen; Peter M. Groffman; Timothy J. Fahey; Melany C. Fisk; Esteban Suarez; Derek M. Pelletier; Robert T. Fahey (Ecosystems, 2004)

Microscopic observations of bacterial sorption in soil cores - A. C. Fisk; S. L. Murphy; R. L. Tate III (Biology and Fertility of Soils, 1998)